Teias ocultas: mapeando redes de autoridade algorítmica nos sites denunciados por desinformação estratégica na CPI da pandemia da Covid-19 - (:unkn) unknown (INSTITUTO BRASILEIRO DE INFORMAÇÃO EM CIÊNCIA E TECNOLOGIA/ UNIVERSIDADE FEDERAL DO RIO DE JANEIRO, 2025)
This study investigates how the media identified in the final report of the COVID-19 Parliamentary Inquiry Commission (CPI) as propagators of disinformation have consolidated themselves as journalistic outlets and manipulated SEO (Search Engine Optimization) strategies, particularly through a network of backlinks (reference links), to build an audience. The study explores how these sites have increased their authority in search engines, gaining visibility and legitimacy in the digital environment, even after being held accountable for harmful practices in Brazil's informational ecosystem. The research analyzes the interconnection between these sites, mapping their backlink networks and examining the relationship between SEO and the construction of authority in contemporary journalism. Analyzing a sample of six sites, the dissertation investigates how search engine optimization practices influence the visibility and legitimacy of alternative media while discussing their implications for the public sphere and democratic debate. Through a combination of monitoring tools to study backlinks, visualization, projection of connection networks, this work proposes a reflection on the impact of disinformation and the new dynamics of journalism in the digital ecosystem.
Keywords: Desinformação online; CPI da Pandemia da Covid-19; Plataformas online; SEO; sustentabilidade do jornalismo; Ciência da informação